1977
DOI: 10.1002/pssa.2210440126
|View full text |Cite
|
Sign up to set email alerts
|

New rhenium containing seignettomagnets and ferroelectrics

Abstract: Complex investigations are made (neutron diffraction study, high temperature X‐ray analysis, dielectric measurements at low and superhigh frequency ranges, resonance (ESR and Mössbauer effect) and magnetic measurements) on the known compounds A2BReO6 (A = Ba, Sr; B = Li, Mg, Ca, Mn, Fe, Co, Ni) and under high pressure synthesized compounds Pb2BReO6 (B = Mg, Fe, Co, Ni) with the perovskite‐type structure. The total sum of the results shows the presence of a spontaneously polarized state in the investigated comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…7 In an attempt to probe further the influence of the A site cation on the structure and properties of these materials, we have investigated the A ) Pb members of A 2 MReO 6 . Formation of perovskite-type Pb 2 MReO 6 for M ) Mg, Mn, Fe, Co, and Ni has been known, 8 but no detailed study of structure and properties has been reported. We have chosen lead as the A-site cation because Pb 2+ with its 6s 2 lone pair is known to influence the structure and properties of AMO 3 oxides.…”
Section: Introductionmentioning
confidence: 99%
“…7 In an attempt to probe further the influence of the A site cation on the structure and properties of these materials, we have investigated the A ) Pb members of A 2 MReO 6 . Formation of perovskite-type Pb 2 MReO 6 for M ) Mg, Mn, Fe, Co, and Ni has been known, 8 but no detailed study of structure and properties has been reported. We have chosen lead as the A-site cation because Pb 2+ with its 6s 2 lone pair is known to influence the structure and properties of AMO 3 oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account these considerations, we have revisited the structure, microstructure and magnetic properties of the Pb 2 NiReO 6 member. 20 In light of our results we have been able to determine the crystal structure and a complex microstructure. We have also established a much more elaborate magnetic behavior which operates on the lead nickel rhenate Pb 2 NiReO 6 perovskite.…”
Section: Introductionmentioning
confidence: 82%
“…It was published elsewhere the synthesis of a complete series of Pb 2 MReO 6 perovskites (M= Ni +3 , Fe +3 , Mn +3 , etc.) [20][21][22] . It was reported that these compounds crystallize in the Fm3m cubic space group with parameter 2a p (where a p ∼ 4Å is the lattice constant of the ABO 3 cubic perovskite).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations